Data Resource Profile: The Social Services Client Administration and Retrieval Environment (SOSCARE) administrative dataset for children’s social care in Northern Ireland - McKenna, Sarah; Murphy, Siobhán; O’Reilly, Dermot; Bunting, Lisa; Maguire, Aideen (International Journal of Population Data Science, 2025)
Introduction Children in contact with the children's social care (CSC) system are a vulnerable group likely to have experienced one or multiple forms of childhood adversity. Understanding the characteristics and social care pathways of these children and their health and social outcomes across the life course is important for informing policy and practice. The Social Services Client Administration and Retrieval Environment (SOSCARE) dataset holds routinely collected CSC data in Northern Ireland (NI). The aim of this data resource profile is to provide an overview of the three key modules in the SOSCARE dataset to act as a guide for researchers. Methods This paper reports selected data contained in the SOSCARE data modules relating to Children in Need, Child Protection Registrations and Children in Care between 1995 and 2015. Information on how to access the data and the strengths and limitations are discussed. Results The SOSCARE dataset is available to approved researchers via the Health and Social Care Honest Broker Service (HSC HBS) in NI and allows researchers to examine population-level interactions with key statutory thresholds of CSC. Between 1st January 1995 and 31st December 2015, the Children in Need module contains data for 148,862 unique children, and the Child Protection Registration and Children in Care modules contain data for 20,355 and 12,335 children respectively. While there are several methodological limitations, the data is a unique and rich resource to examine prevalence and patterns of CSC activity in NI. There is great potential for linkage to other health and administrative datasets to examine predictors of social care involvement and a range of health and social outcomes in childhood and adulthood. Conclusion The SOSCARE data provides detailed case level information on all children in contact with CSC in NI. Research using this data can make an important contribution to evidence-informed policy and practice.